Peranan Komunikasi dalam Perilaku Organisasi pada Reposisi Jabatan Sekolah Tinggi Desain Indonesia - Rizki Maulana Rachman; Tjutju Yuniarsih; Janah Sojanah (Jurnal Komunikasi, 2022)
This study aims to provide an overview of the role of communication in relation to organizational behavior that occurs in the implementation of position repositioning activities in the Indonesian Design College. The role of communication in question shows the success of the leadership in the organization being able to form a structure within the organization with a communication style that is characterized as a liaison for every person in the organization so that there is no jealousy and gaps between the office holders. The role of communication is the object of study in this study which is part of organizational behavior in one of the important activities in the organization, namely position repositioning. Research conducted at the Indonesian Design College also shows the satisfaction of office holders when receiving positions assigned by the leadership as well as the motivation and performance of the organizational structure in carrying out their duties and functions in accordance with their abilities and competencies. The methodology used in this research is descriptive type research through a qualitative approach which is carried out through systematic, actual and accurate written descriptions containing facts and relationships with phenomena that occur with data collection techniques used through questionnaires, interviews, observation and documentation. . The conclusion of this research is the role of communication in organizational behavior shows success in the implementation of job repositioning activities in the organization through the communication process, implementation of internal communication and communication styles as well as identification of effective communication barriers that occur.